2022
DOI: 10.1155/2022/6405772
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study on the Antibacterial Effects of Chlorhexidine‐Loaded Positively Charged Silver Nanoparticles on Enterococcus faecalis

Abstract: This study successfully developed a positively charged silver nanocomplex as a nanocarrier for chlorhexidine (CHX) using ionic liquids. This nanocomplex can interestingly deliver the antibacterial agent with a synergistic effect. In this study, we synthetized and characterized a positively charged silver nanocomplex (AgNPs+) and CHX-loaded positively charged silver nanoparticles (CHX@AgNPs+) using UV-visible spectroscopy, transmission electron microscopy, X-ray diffractometer, Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The use of nanomedicine, along with antibacterial compounds, has been the most promising and overgrowing in recent years. 1 Some nanostructures have intrinsic antimicrobial activity. Therefore, incorporating the antimicrobial agent into the nanocarriers creates an antibacterial nanostructure that can easily pass through the biofilm matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanomedicine, along with antibacterial compounds, has been the most promising and overgrowing in recent years. 1 Some nanostructures have intrinsic antimicrobial activity. Therefore, incorporating the antimicrobial agent into the nanocarriers creates an antibacterial nanostructure that can easily pass through the biofilm matrix.…”
Section: Introductionmentioning
confidence: 99%
“…An aliquot of the solution was analyzed using UV-visible spectrophotometry to track the development of silver nitrate bioreduction. Figures 2 and 3 distinctive display peaks measured at 424 nm for the methanolic extract and 442 nm for the aqueous extract [34,35], respectively. kilimandscharicum methanolic leaves extract, corresponding to a sharp peak (Figure 4).…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…al (2010) showed that the minimum inhibitory concentration (MIC) of ZnO nanoparticles against E. coli is 500 μg/mL [22,23]. Yet, positively charged silver nanocomplexes utilised as nanocarriers for chlorhexidine (CHX) only showed an MIC of 50 μg/mL against E. faecalis, suggesting that ZnO based materials possesses a higher bacterial inhibition capacity as compared to alternative materials [24]. Nevertheless, Jaskova et.…”
Section: Introductionmentioning
confidence: 99%